2014
DOI: 10.2807/1560-7917.es2014.19.33.20880
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial outbreak of staphyloccocal scalded skin syndrome in neonates in England, December 2012 to March 2013

Abstract: Staphylococcal scalded skin syndrome (SSSS) is a blistering skin condition caused by exfoliative toxin-producing strains of Staphylococcus aureus. Outbreaks of SSSS in maternity settings are rarely reported. We describe an outbreak of SSSS that occurred among neonates born at a maternity unit in England during December 2012 to March 2013. Detailed epidemiological and microbiological investigations were undertaken. Eight neonates were found to be infected with the outbreak strain of S. aureus, of spa type t346,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 26 publications
0
3
0
3
Order By: Relevance
“…The prognosis for appropriately treated pediatric SSSS is good, with a reported mortality of less than 5%. [5][6][7][8][9][10][15][16][17][18] In contrast, the mortality rate in adults is very high (40%-63%) despite aggressive treatment, usually due to underlying diseases. 2 Limitations of the study include the retrospective design and heterogeneous clinical descriptions.…”
Section: Complications and Outcomesmentioning
confidence: 99%
“…The prognosis for appropriately treated pediatric SSSS is good, with a reported mortality of less than 5%. [5][6][7][8][9][10][15][16][17][18] In contrast, the mortality rate in adults is very high (40%-63%) despite aggressive treatment, usually due to underlying diseases. 2 Limitations of the study include the retrospective design and heterogeneous clinical descriptions.…”
Section: Complications and Outcomesmentioning
confidence: 99%
“…Although the diagnosis of SSSS is mainly based on clinical manifestation, it can be further con rmed by culturing S. aureus from any suspected primary focus of infection, such as the nasopharynx, periori cial, and diaper area [16]. Many studies pointed out that periori cial and nasopharyngeal cultures are the most likely to be positive, blood cultures are almost negative in children [5,12,[17][18][19][20]. As con rmed by our data, higher positive culture rates were found in periori cial (54.55%) and throat swabs (30.77%) compared with blood samples (5.97%) in the pediatric population, pairwise comparison revealed that there were no differences in the positive culture rates between the periori cial and throat swabs.…”
Section: Discussionmentioning
confidence: 99%
“…Les vaccins contre S. aureus pourraient aussi être proposés aux soignants pour réduire le portage, à condition d'avoir un effet sur le portage, ce qui n'est pas le cas avec les vaccins développés pour l'instant [40]. Le portage de S. aureus qui touche globalement 30 % de la population générale comme décrit plus bas, pourrait être plus élevé chez les soignants [52,53]. Les contacts entre les patients et les soignants porteurs de S. aureus semble faciliter les nouvelles colonisations chez les patients [54,55].…”
Section: Vaccins En Développementunclassified
“…Le risque de transmission entre soignants et patients semble de plus en plus limité du fait des mesures d'hygiène. Néanmoins, des épidémies d'infections à S. aureus ont été décrites avec un soignant comme source de l'infection [52,57,58].…”
Section: Vaccins En Développementunclassified